Disjunction Triggers Exhaustivity Implicatures in 4- to 5-Year-Olds: Investigating the Role of Access to Alternatives. (11th April 2020) - Gotzner, Nicole; Barner, David; Crain, Stephen
Abstract: Children's difficulty deriving scalar implicatures has been attributed to a variety of factors including processing limitations, an inability to access scalar alternatives, and pragmatic tolerance. The present research explores the nature of children's difficulty by investigating a previously unexplored kind of inference—an exhaustivity implicature that is triggered by disjunction. We reasoned that if children are able to draw quantity implicatures but have difficulties accessing alternative lexical expressions from a scale, then they should perform better on exhaustivity implicatures than on scalar implicatures, since the former do not require spontaneously accessing relevant scalar alternatives from the lexicon. We conducted two experiments. Experiment 1 found that 4- to 5-year-olds consistently computed exhaustivity implicatures to a greater extent than scalar implicatures. Experiment 2 demonstrated that children are more likely to compute exhaustivity implicatures with disjunction compared to conjunction. We conclude that children often fail to derive scalar implicatures because (1) they struggle to access scalar alternatives and (2) disjunction (but not conjunction) makes subdomain alternatives particularly salient. Thus, the findings suggest that exhaustivity implicatures can be derived without reference to a scale of alternatives.